Identitas Sosial sebagai Landasan Psikologis Munculnya Prasangka: Kajian Teoretis Psikologi Sosial - Salwi, Annisa Nabihah; Neviyarni, Neviyarni (TSAQOFAH, 2026)
Prejudice is a psychological phenomenon that remains prevalent in social interactions, particularly in plural societies, and is closely related to how individuals construct and interpret their social identities. This article aims to theoretically examine the relationship between social identity and prejudice from a social psychology perspective. The method used is a literature review by analysing relevant theories and previous empirical findings, particularly Social Identity Theory, Self-Categorization Theory, and Realistic Conflict Theory. The review indicates that processes of social categorization, the need for a positive social identity, and ingroup–outgroup dynamics are key mechanisms explaining the emergence and reinforcement of prejudice towards other groups. The article concludes that social identity plays a central role in the formation of prejudice and underscores the importance of a comprehensive conceptual understanding as the basis for developing psychological intervention strategies to reduce prejudice and strengthen social harmony in plural societies.